Triggering language and maths anxiety in non-medical prescribing students. (2nd May 2020) - Smith, Charlotte; Penazzi, Davide
Abstract : Maths anxiety is a debilitating fear of mathematics, which often stems from early learning experiences. Despite their ability to confidently perform complex numerical tasks, such as drug calculations, as an intrinsic part of their role, health professionals often disclose experiencing maths anxiety. Health professionals who have returned to education to study non-medical prescribing are required to undertake a numeracy exam, which can trigger symptoms of maths anxiety. This study explores the use of language in teaching and learning numeracy with non-medical prescribing students, and identifies that use of terminology more closely aligned with health professionals' language results in lower levels of anxiety than using school-like mathematical terminology. The findings of this study can be used to inform supportive teaching practices for health professional educational courses that have a numeracy component.